2022
DOI: 10.1039/d1se01992a
|View full text |Cite
|
Sign up to set email alerts
|

Robust in situ exsolved nanocatalysts on perovskite oxide as an efficient anode for hydrocarbon fueled solid oxide fuel cells

Abstract: In this work, three highly active anode materials are developed to effectively catalyze hydrogen and hydrocarbons in solid oxide fuel cells (SOFCs). A-site deficient (Pr0.5Ba0.5)0.9MnO3-δ materials doped with different Fe...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 67 publications
0
8
0
Order By: Relevance
“…Ru (6 occurrences), Ag (4), Cu (3), and Re (2) only appear in few publications. Nanoparticles comprised of the following are mentioned once each: Au, 100 Bi, 70 Ir, 101 Mo, 58 Rh, 102 (PrBa)O x , 103 and SrO. 104…”
Section: Overview Of Published Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Ru (6 occurrences), Ag (4), Cu (3), and Re (2) only appear in few publications. Nanoparticles comprised of the following are mentioned once each: Au, 100 Bi, 70 Ir, 101 Mo, 58 Rh, 102 (PrBa)O x , 103 and SrO. 104…”
Section: Overview Of Published Workmentioning
confidence: 99%
“…Except for two publications, all collected publications report on mono-metallic or metal–alloy nanoparticles, even though (partial) oxidation of the nanoparticles depending on the gas atmosphere during application is conceivable in many cases. Zhu et al 103 and Ye et al 104 explicitly study oxidic nanoparticles – (PrBa)O x and SrO, respectively.…”
Section: Overview Of Published Workmentioning
confidence: 99%
“…With the increase of global energy consumption as well as environmental concerns, developing green and highly efficient devices for energy conversion is a current research hotspot. Solid oxide fuel cells (SOFCs) can directly release chemical energy stored in fuels into electricity; thus, the conversion efficiency is not limited by the Carnot cycle and can reach up to 70% (45–60% for common fuels such as natural gas with 90% of heat recovery). , The catalytic activity of the anode material is vital to the overall performance of a single cell. Given that the commercial Ni/yttria-stabilized zirconia (Ni/YSZ) anode is reported to suffer from irreversible deactivation due to Ni coarsening and redox instability, , perovskite oxides with in situ exsolved metal nanoparticles (NPs) are recognized as potential SOFC anode materials owing to the structural stability and stronger metal–oxide interface, where the exsolved NPs are socketed into the parent perovskites. …”
Section: Introductionmentioning
confidence: 99%
“…27 It has been reported that metal nanoparticles could also be produced in situ via exsolution from the bulk of the perovskite oxides. [28][29][30] The exsolved nanoparticles are strongly bonded to the host oxides, thus showing a much improved stability. 31,32 The present study was thus intended to enhance the electrochemical activity and durability of a perovskite oxide (La 0.75 Sr 0.25 ) 0.95 Cr 0.5 Fe 0.35 Ni 0.15 O 3Àd (LSCrFN) based cathode via exsolution of NiFe nanoparticles.…”
Section: Introductionmentioning
confidence: 99%
“…27 It has been reported that metal nanoparticles could also be produced in situ via exsolution from the bulk of the perovskite oxides. 28–30 The exsolved nanoparticles are strongly bonded to the host oxides, thus showing a much improved stability. 31,32…”
Section: Introductionmentioning
confidence: 99%